2022
DOI: 10.1002/acn3.51552
|View full text |Cite
|
Sign up to set email alerts
|

Testing awareness in focal seizures: Clinical practice and interpretation of current guidelines

Abstract: The International League Against Epilepsy (ILAE) classification of focal seizures uses recall of experiences post‐ictally to assess for awareness and not ictal responsiveness to external stimuli, stating that responsiveness is often not tested. We investigated how clinicians assess for seizure awareness by administering an online survey. We found that most respondents use both responsiveness and recall to assess for awareness in the clinic (78%) and in the epilepsy monitoring unit (72%). Furthermore, 60% of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Interestingly, the memory recall scores were impaired in both seizures classified as FIAS and FAS based on clinical assessment, indicating that recall of events during seizures may be less reliable than responsiveness testing during seizures for classification of FIAS versus FAS. These findings add to the growing literature suggesting that responsiveness should be formally included in the definition of FIAS versus FAS in addition to memory recall (Contreras Ramirez et al, 2022a, b).…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, the memory recall scores were impaired in both seizures classified as FIAS and FAS based on clinical assessment, indicating that recall of events during seizures may be less reliable than responsiveness testing during seizures for classification of FIAS versus FAS. These findings add to the growing literature suggesting that responsiveness should be formally included in the definition of FIAS versus FAS in addition to memory recall (Contreras Ramirez et al, 2022a, b).…”
Section: Discussionsupporting
confidence: 59%
“…This is a fundamental gap in epileptology will be addressed in the future with assessments that are triggered on seizure detections in real time. [68][69][70]…”
Section: Discussionmentioning
confidence: 99%
“…seizure detections) in real time. [67][68][69] Participants. Seven participants with drug resistant mesial temporal lobe epilepsy were identified and provided written consent in accordance with IRB and FDA requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Another valuable study design would be systematic surveys of clinicians regarding their methods for evaluating awareness during seizures. A recent survey of 11 medical centers in North America with data mainly from epilepsy specialists found that most clinicians use both recall and responsiveness to assess awareness in either the inpatient or outpatient settings; and interestingly, most clinicians incorrectly believe that current ILAE guidelines recommend using both recall and responsiveness to classify awareness during focal seizures [27]. Again, further work is needed including clinicians from broader geographic regions and including non-epilepsy specialists to better understand current widespread clinical practice and to help develop future guidelines.…”
Section: Discussionmentioning
confidence: 99%